Association of in-competition injury risk and the degree of rapid weight cutting prior to competition in division I collegiate wrestlers - Hammer, E.; Sanfilippo, J. L.; Johnson, G.; Hetzel, S. (British Journal of Sports Medicine, 2023)
Objectives: Weight cutting is thought to offer a competitive advantage in wrestling. Dehydration has deleterious effects on physical and cognitive function, which may increase the risk of injury. The purpose of the study was to investigate whether the degree of weight cutting was associated with injury risk.